Cerebrovascular Complications of Vestibular Schwannoma Surgery - Rayan, Tarek; Helal, Ahmed; Graffeo, Christopher S.; Perry, Avital; Carlstrom, Lucas P.; Driscoll, Colin L. W.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Cerebrovascular complications (CVC) are rare consequences of vestibular schwannoma (VS) surgery. Our objective was to assess incidences of findings suggestive of postoperative CVC in a large single surgeon cohort, as well as potential risk factors, and implications.Study Design A cohort of 591 patients was retrospectively reviewed. Postoperative magnetic resonance images were screened for findings suggestive of stroke, T2 hyperintensity in the cerebellopontine angle structures or new encephalomalacia. Clinical records were queried for findings consistent with postoperative CVC.Results In total, 61 patients had radiographic findings consistent with possible postoperative CVC (10%); of them, eight had documented intraoperative vascular injury (1.4%), and four had postoperative clinical exam changes indicative of CVC (0.7%). Clinically manifest intraoperative vascular injuries occurred in four patients and involved the petrosal venous complex (n = 3, 5%) or anterior inferior cerebellar artery (n = 1, 2%); clinical deficits included hemiparesis (n = 1, 2%), facial anesthesia (n = 2, 4%), dysphagia (n = 2, 2%), and unfavorable facial nerve function in two (50%). Three out of four patients in this group required out-of-home placement (75%). Clinical CVCs (n = 4) were not significantly associated with tumor size, tumor cyst, gross total resection, or length of stay. Patients with clinical CVC were significantly more likely to require posthospitalization rehabilitation (19 vs. 75%, p = 0.02; 14 vs. 100%, p = 0.0002).Conclusion Although radiographic findings suggestive of CVC were unexpectedly common in this cohort, intraoperative vascular injury and postoperative clinical CVC were exceedingly rare. The association between unfavorable facial nerve outcome and clinical CVC is likely a marker for more difficult operations, predisposing to higher risk of complications.
Keywords: vestibular schwannoma; stroke; infarct; ischemia; complications